Sophistication, Sentiment, and Misreaction. (27th October 2015) - Chang, Chuang-Chang; Hsieh, Pei-Fang; Wang, Yaw-Huei
Abstract: This study investigates whether the existence or strength of any misreaction in the options market is affected by investor sophistication and investor sentiment. Based on a unique data set of the complete history of all transactions in the Taiwan options market, we find that individual investors exhibit significant misreaction to information and that this misreaction becomes stronger during periods of high investor sentiment. In addition, more active or aggressive individual investors always exhibit misreaction and do not learn from their past mistakes. Our empirical results are robust to alternative measures of investor sentiment and definitions of long- and short-term horizons.